2017
DOI: 10.4103/jispcd.jispcd_384_17
|View full text |Cite
|
Sign up to set email alerts
|

Mother's work status on children's bruxism in a subset of Saudi population

Abstract: Aims and Objectives:The aims and objectives of this study were to determine if an association exists between mothers work status and her children's incidence of bruxism and habits related to bruxism.Materials and Methods:A cross-sectional study was conducted through data collection of a questionnaire answered by 561 mothers’ about their working status and their child's habits and behaviors. The survey consisted of 5 parts with a total of 34 questions: mother's information, child's behavior, child's sleeping pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 37 publications
0
10
0
5
Order By: Relevance
“…In a study based in Tehran, nail biting was the most frequent habit with a prevalence of 12.5% [14]. Consequently, a study conducted in Saudi Arabia reported the prevalence of sleep bruxism was 37.6% with the most common oral habit [15]. Nail biting is often associated with anxiety or stress, and the trend of higher prevalence of nail biting practices as age increases could be linked to the challenges children face stressful conditions.…”
mentioning
confidence: 99%
“…In a study based in Tehran, nail biting was the most frequent habit with a prevalence of 12.5% [14]. Consequently, a study conducted in Saudi Arabia reported the prevalence of sleep bruxism was 37.6% with the most common oral habit [15]. Nail biting is often associated with anxiety or stress, and the trend of higher prevalence of nail biting practices as age increases could be linked to the challenges children face stressful conditions.…”
mentioning
confidence: 99%
“…21 Oral habits, such as nail biting, are also twice more likely to be reported in children with possible SB than without SB through parental reports. 7 Nocturnal agitation and nightmares were also associated with possible SB in children. 25 Some respiratory conditions, like asthma, snoring, respiratory allergies, adenotonsillar hypertrophy and obstructive sleep apnoea are shown to be associated with SB in children and adolescents (see Figure 2).…”
Section: Risk Factorsmentioning
confidence: 98%
“…based on parental reports) ranges from 25.2% to 34.5% in school aged children. [6][7][8][9] In teenagers, between 10 and 19 years old, the possible SB prevalence is reported at 52.9%. 10 In a retrospective study, the prevalence of possible SB across ages was 20.7% in children 0-6 years old, 19.4% in children 7-11 years old and 14.6% in children 12-17 years old, with no gender difference.…”
Section: Prevalence/incidencementioning
confidence: 99%
See 2 more Smart Citations